Value of Glypican-1 Expression in Pleural Epithelioid Mesothelioma, Adenocarcinoma and Squamous Cell Carcinoma of the Lung - ED Hassab El-Naby, Noha; Saber Mohammed Ahmed, Mohsen; Ahmed, Nagwa Abd El-Sadek (Asian Pacific Journal of Cancer Biology, 2023)
Background: Distinguishing between pleural epithelioid mesothelioma, lung adenocarcinoma, and poorly differentiated squamous cell carcinoma (SCC) is a challenge in some cases. A panel of markers has been recommended by the International Mesothelioma Interest Group (IMIG) guideline to differentiate epithelioid mesothelioma from lung adenocarcinoma and SCC. However, the use of novel highly specific immunohistochemical (IHC) markers is still required. Objectives: This study aimed to evaluate glypican-1 (GPC1) expression in epithelioid mesothelioma, lung adenocarcinoma, and SCC, correlating its expression with some known clinicopathological parameters to clarify its diagnostic and prognostic value. Methods: This study included seventy specimens designated as 20 cases of pleural epithelioid mesothelioma, 30 cases of lung adenocarcinoma, and 20 cases of lung SCC. GPC1 expression was evaluated using immunohistochemistry (IHC). The data was analyzed statistically by SPSS software 25. GPC1 expression was correlated to different clinicopathologic data using Chi-square test. The study was conducted according to local Ethical Committee regulations. Results: This study detected positive GPC1 reactivity in all cases (100%) of pleural mesothelioma and lung SCC, in which increased GPC1 expression was correlated to large-sized, high grade, advanced stage tumors, and the presence of lymph node metastasis (LNM). In contrast, GPC1 expression was absent in about 93% of lung adenocarcinoma cases, and only 2 cases exhibited weak focal expression. Conclusion: Our findings demonstrated that GPC1 expression is upregulated in advanced pleural mesothelioma and pulmonary SCC; tumors with high GPC1 expression exhibited more advanced biological behavior.